Türkiye’de ekonomik olgular bağlamında Türk basın sektöründe dağıtım ve sorunları - Balfidan, Haşmet Mahir (My University, 2003)
Objactive of this study is to analise the devolopment of delivery of written press which is known to be 4'th power after the first three;legislation,verbal and lawsuit.That are unenmity powerof democratic publics.To determine problems and to analize what is passible to increase circulation by means of manegende changes. Although daily written press has came through for about 172 year since 'Takvimi Vakayi'.which is assved to be the very first Turkih newspaper and newspapers have impored pretty much with regend to number and qualty.They couldnt reach much desired circulation numbers .Once the reasans for circulation to be steady and even sametimes lower are anelyaed,it is understood that the inadequate systems and personel in delivery processis one of the main reasons. Nowadays,all of three methods;dealer postal service and deliver to house system are aplied in our country like all other countries.But the most populer distribition system is the dealer one in our country.The contry that has high rotra of reades,are applied the deliver to hause system or postal service,instensvely. Especially deliver to hause system that is more activity and easy to control are applied Japan seems a national solutien by puting in order again in Turkey's condition instead of the distribution system of deliversthat is more difficult to controll the sellin and increasing the ratie of giving book. This study has four parts.The first parts is examined carefully the press management and the time that is nesassery to complain the pressproduet in Turkey.The other parts is examined carefully,the distribution of press products the organization of the distribution press managements in Turkey.

Bu çalışmanın amacı demokratik toplumların vazgeçilmez erklerinden olan yasama ,yürütme ve yargıdan sonra gelen ve dördüncü erk olarak bilinen günlük yazılı basın dağıtımının Türkiye'deki gelişim sürecini irdelemek sorunları belirlemek ve yönetsel değişikler ile tirajı arttırabilme konusunda neler yapılabileceğini analiz etmektir. Ülkemizde günlük yazılı basın ilk Türkçe gazete olarak kabul edilen Takvim-i Vekay-i'den bu yana yaklaşık 172 yıl gibi bir süre geçmesine ve bu süre içerisinde gazetelerin nicelik ve nitelik açısından gelişmelerine rağmen toplam tiraj açısından istenilen düzeye ulaşamamıştır.Türkiye'de aynı düzeyde seyreden tirajın yükselmemesi ve zaman zaman aşağı düzeye inmesinin nedenleri araştırıldığında en belirgin nedenlerden biri olarak Türk basın sektöründe pazarlama öne çıkmaktadır.Bununla birlikte dağtımda yanlış sistem kullanımı ve sorunları önemli etkenlerdendir. Günümüzde bütün ülkelerde uygulanan bayi,elden dağıtım ve posta yolu ile dağıtım yöntemlerinin her üçü de ülkemizde uygulanmakta,ancak bunlardan en yaygın olarak bayiler aracılığı ile dağıtım sisteminin tercih edildiği gözlemlenmektedir.Bu konuda okuyucu oranları yüksek ülkelerde,yoğun olarak elden dağıtım veya posta ile dağıtım uygulanmaktadır. Çalışma dört bölümden oluşmaktadır. İlk bölümde basın işletmeleri ve Türkiye'de basılı ürün oluşma süreci incelenmektedir. Daha sonraki bölümlerde de basılı ürünlerin dağıtımı,gazete ve dergi dağıtım sistemi,Türkiye'de basın dağıtım işletmelerinde organizasyon alt başlıklar sunularak incelenmektedir.
Keywords: Basılı ortamlar; Basın; İletişim; Medya (İletişim araçları); Toplum bilimleri; Toplumsal etkileşim